When do the effects of single‐session interventions persist? Testing the mindset + supportive context hypothesis in a longitudinal randomized trial - Cameron A. Hecht; Samuel D. Gosling; Christopher J. Bryan; Jeremy P. Jamieson; Jared S. Murray; David S. Yeager (Wiley, 2023)
Abstract Background Single‐session interventions have the potential to address young people's mental health needs at scale, but their effects are heterogeneous. We tested whether the mindset + supportive context hypothesis could help explain when intervention effects persist or fade over time. The hypothesis posits that interventions are more effective in environments that support the intervention message. We tested this hypothesis using the synergistic mindsets intervention, a preventative treatment for stress‐related mental health symptoms that helps students appraise stress as a potential asset in the classroom (e.g., increasing oxygenated blood flow) rather than debilitating. In an introductory college course, we examined whether intervention‐consistent messages from instructors sustained changes in appraisals over time, as well as impacts on students' predisposition to try demanding academic tasks that could enhance learning. Methods We randomly assigned 1675 students in the course to receive the synergistic mindsets intervention (or a control activity) at the beginning of the semester, and subsequently, to receive intervention‐supportive messages from their instructor (or neutral messages) four times throughout the term. We collected weekly measures of students' appraisals of stress in the course and their predisposition to take on academic challenges. Trial‐registration: OSF.io; DOI: 10.17605/osf.io/fchyn. Results A conservative Bayesian analysis indicated that receiving both the intervention and supportive messages led to the greatest increases in positive stress appraisals (0.35 SD; 1.00 posterior probability) and challenge‐seeking predisposition (2.33 percentage points; 0.94 posterior probability), averaged over the course of the semester. In addition, intervention effects grew larger throughout the semester when complemented by supportive instructor messages, whereas without these messages, intervention effects shrank somewhat over time. Conclusions This study shows, for the first time, that supportive cues in local contexts can be the difference in whether a single‐session intervention's effects fade over time or persist and even amplify.